Discussion activities, teacher beliefs, and the learning of mature, low attaining students - Swan, Malcolm (NOMAD Nordic Studies in Mathematics Education, 1998)
This two-year investigation evaluated strategies for learning mathematics with low-attaining students in Further Education (FE) colleges in England. A substantial collection of discussion activities were developed to enhance metacognitive activity where conceptual obstacles were identified and targeted. A pre-test-post-test design was combined with detailed classroom observation. Two 'constructivist' teachers, sympathetic to metacognitive teaching approaches are compared with two' transmission' teachers who preferred exposition and practice. In the first year, without intervention, students showed modest gains with no clear difference between the two pairs of teachers. In the second year, the discussion activities contributed to statistically significant gains among the 'constructivist' teachers, but little difference was observed with the 'transmission' teachers.